Relationship of Nutritional Concerning Families with the Nutritional Status of Children In the Working Area of Local Public health center - Suci Fitri Rahayu (Healthy-Mu Journal, 2021)
The status of malnutrition and malnutrition is caused by various interrelated factors, including family behavior factors in providing food, breastfeeding and complementary feeding, and nutrition service efforts. This study aims to analyze the relationship between nutritionally conscious families (Kadarzi) and the nutritional status of children under five in the Work Area of the Puskesmas Pelambuan, Banjarmasin. This study used an analytic method with a cross sectional approach. The sampling technique used was proportional random sampling with a sample size of 82 parents of children under five. The measuring instrument used was a questionnaire and observation with weighing tools, the data analysis used the Spearman rank test. The location of this research was conducted in the Working Area of the Pelambuan Health Center, Banjarmasin City. Based on the results of the study, families who were aware of nutrition tended to have normal nutritional status totaling 27 (79.4%) and more than 7 (20.6%). Meanwhile, families who were not aware of nutrition tended to have malnutrition status, amounting to 31 people (64.6%) and malnutrition status 17 (35.4%). The spearman rank statistical test obtained p value 0.000 smaller than α = 0.05. There is a relationship between nutritionally conscious families (adarzi) with the nutritional status of children under five in the working area of Puskesmas Pelambuan, Banjarmasin City. Keywords : Nutritional awareness family, nutritional status, children